Modeling of Sustainable Marine Resources: Case Study Sampan Tribe in Riau Island, Indonesia - Andesta Indah (EDP Sciences, 2021)
Currently, massive practice in fisheries caught and lack of marine ecosystem is not the only news in Indonesia but also in most other countries. Those practices are based on compliance with the growing food needs due to the growth of the world’s population. The Riau Island, known as the Sampan Tribe, has been practicing methods and maintaining a sustainable marine ecosystem from generation to generation for decades. The focus of this research is on the Sampan tribe and the practice of sustainable marine resources. To understand the interactions and activities, culture, values by the Sampan tribe to maintain harmony with the sea and marine ecosystems. It shapes modeling of sustainable marine resources. To gain the best of modeling the Sampan tribe using qualitative method. The researchers did the deep interview with the key of informant from sampan tribe in the land, observation the three areas which was Berakit Bintan, Kampung Tua Batam, and Belakang Padang Batam. To support the data, the researcher did a literature study related to the sea, sampan tribe, and coastal ecosystem. The Sampan tribe consists of three practices, namely the practice of fishing gear, marine ecosystem sustainability practice, and the practice of prohibiting the catching marine animals. They believe that maintaining the sustainability of the marine ecosystem will have an impact on fish survival. It followed by a ban on catching several types of marine animals such as dugongs, turtles, dolphins, and whales. In fishing, the Sampan tribe protects the spawning fish, and the size of the fish is not caught. Their practices are in line with the government policies regarding the catching of fish, fishing gear, and protected marine animals. To conclude, the Sampan tribe is one of the drivers for supporting sustainable marine resources with practices and it is believed to be able to save the sea and existence as a Sampan tribe.